ANALISIS PENGARUH KEPEMIMPINAN, DISIPLIN KERJA, DAN LINGKUNGANN KERJA, TERHADAP KINERJA PADA FAKULTAS KEDOKTERAN UNIVERSITAS SEBELAS MARET SURAKARTA - Ade Atik Nurrohmah; Sri Hartono; Istiqomah Isttiqomah (ITB AAS INDONESIA Surakarta, 2019)
The aim of thisSstudyStoSanalyze the influenceGoFleadership, WworkRdiscipline,Uand workEenvironment OonUemployeeGperformance Uat Sebelas Maret University Surakarta. This study uses quantitative methods and Kmultiple Mlinear Kregression analysis. KThe population Kin this Kstudy KwasK60 Hpeople. HThEEresultRs of Rthis studyR indicate Ythat KLeadership,[WorkODiscipline, andJWorkHEnvironment Ksimultaneously Lor LjointlyL haveaapositive,effect oniEmployeeiPerformance. jVariable work discipline has a dominant influence compared to leadership variablesgand gworkgyenvironmentuon uemployeepperformance. As evidenced by the magnitude of the coefficient price for work discipline variables of 5.173 greater than the coefficient of leadership variables H of 2.235 and the coefficient of the work environment of 3.835 Keywords : Leadership , Dicipline, Work environment